THU0138 The acute phase response does not fully explain dyslipidemia and insulin resistance in inflammatory arthritis. (1st June 2001) - Dessein, PH; Joffe, BI; Stanwix, AE; Moomal, Z
Abstract : Background: An increased frequency of insulin resistance (IR) and dyslipidemia has been identified in inflammatory arthritis (IA). These metabolic disturbances may be attributable to disease activity and were implicated in the excess cardiovascular disease mortality as reported in IA. Objectives: In the present study we evaluated insulin sensitivity and lipid metabolism, as well as the potential role of the acute phase response as a predictor of these metabolic disturbances in IA. Methods: Eighty seven patients (38 rheumatoid arthritis, 29 spondyloarthropathy, 20 undifferentiated inflammatory arthritis) and 30 age-, gender- and race matched healthy controls (CN) were enrolled. Patients who had taken glucocorticoids during the previous 2 months or were taking agents known to affect insulin sensitivity or lipid metabolism were excluded. The body mass index (kg/m 2 ) was calculated in each subject. The erythrocyte sedimentation rate (ESR), plasma glucose, serum insulin and total cholesterol (chol), LDL-chol, HDL-chol and triglycerides were determined on fasting blood samples. IR was estimated by the homeostasis model assessment (HOMA). Results were expressed as mean (SD). Results: The BMI was 26.5 (4.2) in the patients and 22.9 (2.8) in the CN (p < 0.001). The HOMA (uU.mmol/ml.l) was 1.9 (1.3) in patients as compared to 1.1 (0.5) in CN (p = 0.001). The HDL-chol was lower (p = 0.002) and the total chol/HDL-chol was higher (p < 0.001) in patients as compared to CN. Only after controlling for the BMI in addition to the ESR, was the HOMA no longer different between patients and CN. The ESR and HOMA, but not the BMI, significantly predicted (p < 0.05) high chol/HDL-chol ratios. However, after controlling for these variables, this lipid parameter remained different in patients as compared to CN. Also, IA was associated with a positive family history for premature coronary artery disease (p < 0.03). Conclusion: Metabolic disturbances were identified in the majority of our patients and should therefore be addressed in the management of IA. IR could be attributed to the acute phase response and excess weight. However, dyslipidemia was associated with IA independent of the ESR, BMI and IR. Dyslipidemia may constitute a risk factor for IA. References: Svenson KL, et al . Metabolism 1988;37:125–30 Park YB, et al . J Rheumatol. 1999;26:1701–4 Dessein PH, et al . Rheumatology 2001, in press